ANALISIS PENERAPAN DISCOVERY LEARNING BERBANTUAN MEDIA FLASHCARD PADA PEMBELAJARAN IPAS KELAS 3 SEKOLAH DASAR - Shintya, Bella; Nanda Faradita, Meirza; Adi Putra, Deni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the application of flashcard media assisted by the Discovery Learning model in supporting science learning at the elementary school level and to provide a new learning method that can be applied in the classroom. Science learning which is still dominated by lecture methods makes students less active and has difficulty understanding concepts concretely. Therefore, this study uses a qualitative descriptive approach with data collection methods in the form of observation, interviews, and documentation. The research subjects included class teachers and third-grade students, with the main focus on the implementation process and the impact of using flashcard media in each Discovery Learning syntax. Data analysis techniques through the stages of data collection, data reduction, data presentation, and drawing conclusions. The results of the study show that students gave a positive response to the implementation carried out. This is evident from the increased enthusiasm and activeness of students during the learning process. In addition, the use of flashcards helps students understand science material more easily, interestingly, and concretely. The application of the Discovery Learning model in collaboration with flashcard media can be an alternative new learning method applied by teachers in the classroom.